1963
DOI: 10.19182/remvt.7223
|View full text |Cite
|
Sign up to set email alerts
|

Contribution à l'étude des Tabanidae (Diptera) d'Afrique centrale : les Tabanidae de la République Centrafricaine

Abstract: cf. fichier PDF de l'article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…These surveys, conducted from 2015 to 2017, led to the identi cation of 25 species, much less than the 84 species recorded in the preliminary study of 1970 [17]. However, 8 species not previously recoded in Cameroon were identi ed, including: Tabanus Latipes Macquart, 1838 (1 ), Tabanus ricardae Surcouf, 1906 (1 ), Tabanus fasciatus Fabricus, 1775 (32 , 6 ), Haematopota pluvialis Linnaeus, 1758 (18 ), Haematopota decora Walker, 1850 (19 , 3 ), Haematopota nigripennis Austen, 1914 (18 ), C. distinctipennis Austen, 1906 (47 , 5 ) and Ancala fasciata Fabricus, 1977 (34 , 7 ). The new species record increases the list of the Tabanidae identi ed in Cameroon to 92 species and is higher than that reported in the other countries within the Afro-tropical region, including Central African Republic [18], Ivory…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These surveys, conducted from 2015 to 2017, led to the identi cation of 25 species, much less than the 84 species recorded in the preliminary study of 1970 [17]. However, 8 species not previously recoded in Cameroon were identi ed, including: Tabanus Latipes Macquart, 1838 (1 ), Tabanus ricardae Surcouf, 1906 (1 ), Tabanus fasciatus Fabricus, 1775 (32 , 6 ), Haematopota pluvialis Linnaeus, 1758 (18 ), Haematopota decora Walker, 1850 (19 , 3 ), Haematopota nigripennis Austen, 1914 (18 ), C. distinctipennis Austen, 1906 (47 , 5 ) and Ancala fasciata Fabricus, 1977 (34 , 7 ). The new species record increases the list of the Tabanidae identi ed in Cameroon to 92 species and is higher than that reported in the other countries within the Afro-tropical region, including Central African Republic [18], Ivory…”
Section: Discussionmentioning
confidence: 99%
“…Haematopota Meigen, 1904 H. pluvialis Linnaeus, 1758 (18 ) Type-locality: Only females of this species were caught with Nzi traps set in the mosaic forest (5°33972' N and 14°188' E) precisely in the Gabong type-locality of the East region (Fig. 5b).…”
Section: ) Tabaninae Latreille 1802mentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from preliminary studies that reported 62 [ 21 ] and 84 [ 23 ] species respectively, there appear to have been no updates on their checklist and distribution. A survey in the Central African Republic indicated that 54 to 64 species constituted the tabanid fauna of this country [ 24 ]. The updated checklist of tabanids of the Ivory Coast reported the occurrence of 70 species [ 25 ], whereas 49 tabanid species are found in Algeria [ 26 , 27 ] as confirmed in a recent update [ 28 ].…”
Section: Introductionmentioning
confidence: 99%